Results 1 to 3 of 3

- Mar 20th 2011, 03:03 AM #1

- Joined
- Jan 2011
- Posts
- 104

## (6)/(x^2 - 3x) - (5)/(2)(3-x)

Hi guys, need help on this question

My working:

(6)/(x^2-3x) - (5)/(2)(3-x) = (6)/(x)(x-3) - (5)/(2)(3-x)

= - (6)/(x)(3-x) - (5)/(2)(3-x)

= -6(-2)-5(-x)/2x(3-x)

= (12+5x)/(2x)(3-x)

Answer = (5x+12)/(2x)(x-3)

What is wrong with my working?

P.S sorry that it's a bit messy, I don't know how to make it into that "mathematics" form.

- Mar 20th 2011, 03:32 AM #2

- Mar 20th 2011, 03:47 AM #3

- Joined
- Jan 2011
- Posts
- 104